Types of suicide pacts: a comparative analysis using the National Violent Death Reporting System - Kim, Kawon Victoria; Russell, Cayley; Kaplan, Mark S.; Rehm, Jürgen; Lange, Shannon (Frontiers in Psychiatry, 2023)
Introduction Suicide pacts are lethal acts of violence involving multiple decedents. No study has ever compared suicide pact types using a large sample, limiting our understanding of this rare but serious phenomenon. The objective of the current study was to describe suicide pacts in the United States and empirically compare suicide pacts wherein all decedents died by self-harm with those that involved assisted suicide. Methods Using restricted access incident-level data from the National Violent Death Reporting System, we identified 277 suicide pact incidents (225 suicide pacts wherein all decedents died by self-harm and 52 suicide pacts wherein one pact member died by assisted suicide). The two suicide pact types were compared for demographics, pact characteristics, and preceding circumstances. Results Compared with decedents of suicide pacts involving assisted suicide, decedents of suicide pacts wherein both members died by self-harm had significantly lower odds of being non-white, Hispanic or non-Hispanic (OR = 0.33, 95%CI: 0.18, 0.64), using an active method of suicide (i.e., ICD-10 codes X70-X83) (OR = 0.01, 95%CI: <0.01, 0.04), and experiencing interpersonal relationship problems (OR = 0.48, 95%CI: 0.27, 0.87) and a crisis within two weeks of their death (OR = 0.58, 95%CI: 0.36, 0.97), but greater odds of preceding physical health problems (OR = 3.25, 95%CI: 1.84, 6.04). Discussion Overall, our findings indicate that suicide pacts wherein all decedents died by self-harm and suicide pacts that involved an assisted suicide appear to have largely distinct profiles. While further research is required, the discrete characteristics of these two types of suicide pacts have important implications for prevention.